Recent advances in population improvement through RGA under Irrigated Boro rice breeding program in Bangladesh (Bangladesh Rice Journal, 2023)
Development of new high yielding varieties needs highly accelerated breeding approaches to meet the demand of increased rice production now a days. To address this issue, Rapid Generation Advance (RGA) of segregating rice population and Line Stage Testing (LST) of fixed breeding lines has been adopted as a routine work in Bangladesh Rice Research Institute.   In the present study, we described the evidence of advancing a large number of segregating population and high selection pressure at LST to isolate fixed lines in the Irrigated Boro rice breeding program. This program was implemented under development of Favourable Boro Rice and Cold Tolerant Rice. In both programs, wide variation was observed among the number of population and segregating generation at RGA nursery. A total of 62,269 individual progenies from 64 crosses were advanced through RGA in 2019 whereas 12,122 individual progenies from 45 crosses were advanced in 2020 under the FBR program. In contrast, 68,531 segregating progenies from 82 crosses and 15,004 progenies from 52 crosses were advanced through RGA under CTR program during 2019 and 2020, respectively. During LST, selection pressure was imposed for the first time to isolate homozygous lines from a pool of large number of breeding lines. The selection intensity ranged between 0.21-20.1% and 0.6-14.9% for FBR and CTR, respectively. A total of 794 fixed breeding lines having different combinations of favourable alleles of BLB, Blast and different grain quality traits were isolated from 17,633 RGA derived lines. The results obtained from this study suggested that the RGA system has become an effective tool for population improvement in a breeding program.Bangladesh Rice J.26 (1): 33-46, 2022